Full-text publication outcomes of oral abstracts presented at the Turkish National Pediatric Congresses - Akgül, Sinem; Başaran, Özge; Pehlivantürk Kızılkan, Melis; Ütine, Gülen Eda; Akcan Yıldız, Leman; Yıldız, Yılmaz; Düzova, Ali; Hasanoğlu, Enver (The Turkish Journal of Pediatrics, 2026)
Background. Scientific congresses are critical platforms for knowledge dissemination and collaboration. The scientific value of presented abstracts is best demonstrated through their subsequent publication as full-text articles in peer-reviewed journals. This study aimed to evaluate the publication rate and characteristics of oral abstracts presented at the Turkish National Pediatric Congresses (TNPC) between 2019 and 2023. Methods. Abstract books of five consecutive congresses were reviewed. The publication status of each abstract was determined through systematic searches in Web of Science, PubMed, Scopus, Google Scholar and the TR Index utilizing the title, keywords from the title and author names. Parameters such as study design, collaboration type, index status and the impact factor of the journal, the year it was published, and time to publication were analyzed. Additionally, the subspecialty of each abstract and the publication rate for each subspecialty were evaluated. Results. Among 268 oral abstracts, 111 (41.8%) were published as full-text articles. Of these, 66 (59.5%) were published in journals indexed in the Science Citation Index Expanded. Approximately one-third (32.4%) of the articles were published in Q1 or Q2 ranked journals. The average impact factor was 1.72 ± 1.26 and the mean time to publication was 1.6 ± 1.17 years. The most common study design published was retrospective (51.3%), and the majority were single-center studies (88.3%). The highest publication rates were observed in the fields of rheumatology, adolescent medicine, and infectious diseases. Conclusion. A significant portion of the papers presented at TNPC congresses are published in peer-reviewed scientific journals. The fact that more than one-third of the published studies appear in high-impact journals demonstrates the academic quality of the papers presented at the congresses and the effectiveness of the selective evaluation process. The findings provide valuable contributions to the monitoring and development of academic productivity in the field of pediatrics in Türkiye.